Complexos de paládio(II) e platina(II) com oxadiazois funcionalizados com diaminas: síntese, caracterização e atividade biológica - Lara Vieira de Almeida Peçanha (2024)
Cancer is the second leading cause of death worldwide. According to the WHO, approximately 20 million new cases were reported in 2022 alone. Despite the great success of cisplatin in treating various types of cancer, its adverse effects highlight the need for new, more effective drugs for treating the disease. Metal complexes have been extensively studied due to the promising results in both in vitro and in vivo studies. Moreover, the use of biologically active functional ligands can help reduce the toxicity of these complexes, enhancing their antitumor activity without harming healthy cells. Therefore, this study aimed to develop four novel Palladium(II) and Platinum(II) complexes containing ligands composed of thiophene, oxadiazole, and diamines, with the goal of obtaining potential antitumor agents. The ligand classes used have already demonstrated proven biological activities in the literature and as promising candidates for cancer treatment. The ligands were characterized by nuclear magnetic resonance (NMR) and infrared vibrational spectroscopy to confirm their structures and stability. In addition to the techniques mentioned above, the complexes were also characterized by elemental analysis, Raman spectroscopy, and mass spectrometry. The results obtained indicate the formation of neutral complexes of the type [M(II)L2Cl2], with good yield and satisfactory purity for the described syntheses. The cytotoxic activity of the synthesized compounds was evaluated against the tumor cell lines MDA-MB-231 (human metastatic breast adenocarcinoma) and 4T1 (murine mammary carcinoma) and the healthy cell line MCF-10 (normal mammary gland cells). Three of the four synthesized complexes showed that metal coordination improved antiproliferative activity. To understand the structure-activity relationship, the interaction between the complexes and the biomolecules DNA and BSA was evaluated through spectrophotometric studies and agarose gel electrophoresis. Spectrophotometric titration studies showed moderate interaction between DNA-complexes and strong interaction between BSA-complexes. The electrophoresis experiment revealed that three of the four complexes interact with DNA, altering the conformation of the plasmid. Theoretical optimization and stability studies by NMR were performed to investigate the behavior of the platinum complexes in DMSO solvent. Finally, in silico ADME studies were also conducted for all synthesized complexes and showed that all comply with Lipinski's rules, possess good lipophilicity, and inhibit CYP enzymes.